Translators as publishers: exploring the motivations for non-profit literary translation in a digital initiative - Marin-Lacarta, Maialen; Vargas-Urpí, Mireia (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
Motivations for volunteering have rarely been studied in the context of professional literary translators. Instead, studies have mainly focused on amateur translators in areas such as charities, fansubbing, TED, Wikipedia, Skype and Facebook. This paper explores this under-researched topic in the context of ¡Hjckrrh!, a non-profit publisher led by translators who self-publish literary translations in e-book format. As of March 2018, ¡Hjckrrh! had issued 21 e-books translated from seven languages, with the collaboration of fourteen translators. Most of the translators are experienced professional translators with full-time jobs. Based on in-depth semi-structured interviews with fifteen participants, this paper explores the translators’ motivations for collaborating on this initiative and shows how an ethnography-inspired methodology can be fruitful when studying translators. The outcomes reflect that translating for pleasure and personal relationships are factors that trigger translators’ voluntary participation in ¡Hjckrrh!, and the conclusions highlight the need for more research into similar non-profit publishing initiatives.